Upaya Meningkatkan Kemampuan Kognitif melalui Metode Bermain dengan Media Puzzle Angka - Ni Komang Ayu Sri Lestari; Nihlawati Nihlawati; Maria Magdalena Meo (Universitas Nusa Cendana, 2021)
The problems found in this study regarding the introduction of low cognitive ability in numbers. The purpose of this research was to study the improvement within cognitive ability in the introduction of numbers after the application of the playing method using the number puzzle media to the B1 group children during the second semester or the academic year 2020/2021 in TK Negeri Pembina Kecamatan Dawan. This type of study is a classroom action-based research which was carried out in two cycles with 15 children as the subjects during the second semester or the academic 2020/2021. The data on the cognitive in the introduction of numbers were collected by observation method with observation forms as the instrument. The data in this study were analyzed using descriptive statistical analysis method and quantitative descriptive analysis method. The result of the data analysis shows that there was 70,5% improvement for the cognitive ability in the introduction of numbers with the application of the playing method in the first cycle, which can be categorized as average. An improvement into 87,16% was also found in the second cycle which can be categorized as high.